First record of Prionocrangon Wood Mason & Alcock, 1891 (Crustacea: Decapoda: Caridea: Crangonidae) in the East Pacific and description of a new species from western Mexico - Hendrickx, Michel E.; Ayón-Parente, Manuel (Zootaxa, 2012)
A new species of the rare genus Prionocrangon is described from the central Gulf of California, Mexico. This is the firstrecord for this genus of Crangonidae in the east Pacific which is otherwise widely distributed in the Atlantic, Pacific andIndian oceans. Prionocrangon incisum sp. nov. differs from all other known species of Prionocrangon by the presence ofa deep notch near the posteroventral margin of the sixth abdominal somite. Presence of post-embryonic larvae in one partly spent female indicates that P. incisum sp. nov. exhibits abbreviated larval development.